Post Method Language Teaching Within the Implementation of 2013 Curriculum - Hervina Hervina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This research aims to find out know the problem in implementing the 2013 curriculum and offers an alternative solution to this problem by incorporating several principles of post method language teaching. The data were collected through the interview with the English teachers in SMPN 1 Malalak regarding the obstacles they faced in the 2013 curriculum implementation. The data were qualitatively analyzed and the principles of post method language teaching were descriptively incorporated into the problems found in order to provide their alternative solutions. The research findings reveal that the problems of implementing the 2013 curriculum in this school are teachers’ unreadiness, students’ low level, and application of scientific approach and that the post method language teaching can serve as an alternative solution since it allows more flexibility in the learning process through involving students’ and teachers’ in the process. In conclusion, the issues in the implementation of 2013 curriculum come from the teachers’ and students’ as well as the teaching method required to be applied by curriculum. To overcome this, the teachers can apply the principle of post method language teaching in the learning process. Keywords: 2013 Curriculum, Implementation, Post Method Language Teaching